Arbitration of Islamic finance disputes in Malaysia: a SWOT analysis - Oseni, Umar Aimhanosi; Abdul-Qadir Zubair, Aishat (2014)
Malaysia, apart from being recognised as a global hub for Islamic finance, is gradually emerging as a major arbitration hub in the Asia-Pacific region. While there are other world-class arbitral institutions in the region, Malaysia stands a chance to lead the region when it comes to Islamic finance arbitration. Therefore, in order to examine the suitability of arbitration with Islamic finance disputes, considering recent reforms in the legal and regulatory framework in Islamic finance in Malaysia, this study adopts the SWOT analysis method, namely, the Strength-Weakness-Opportunity-Threat model. It analyzes the needs and expectations of the parties (bankers and customers) vis-à-vis the existing legal framework for arbitration in Malaysia. The Arbitration Act 2005 is the principal law that regulates all arbitral proceedings in Malaysia; and for arbitration involving Islamic finance transactions, the Kuala Lumpur Regional Centre for Arbitration has issued its i-Arbitration Rules 2013 under which a number of arbitral disputes have been resolved. The paper concludes that for Malaysia to become the preferred forum for settlement of Islamic finance disputes, particularly those that emanate from cross-border transactions, it needs to address number of threats that currently stare at the practice of arbitration in the country.